Batch extraction of caffeine from cocoa MCBC 1 - Nuradibah, Hussin (2010)
Caffeine is naturally occurring substances found in the leaves seeds of fruits of a group of compounds known as methylxanthines. The most commonly known source of caffeine is coffee and cocoa seeds. However, cocoa seeds have received limited attention as a source for caffeine since it widely used as a source to make a cocoa powder and chocolate. The caffeine extraction from cocoa seeds will be another way to fulfill demand for caffeine. The objectives of this research is to extract the caffeine from Cocoa MCBC I Seeds by the effect of different extraction time, particle size of cocoa seeds powder and ratio of cocoa seeds-solvent towards yields of caffeine by using batch system. This research was divided into five main steps which are the sample preparation, leaching of caffeine, liquid-liquid extraction, drying of caffeine and analysis the crude caffeine using High Performance Liquid Chromatography (HPLC). Extraction yield increase towards the increasing of extraction time. Meanwhile, extraction yield of caffeine increased when using the smallest particle size of cocoa. However, the best ratio of cocoa seeds-solvent to get the highest extraction yield was 1:5. Besides that, either using lower ratio or higher ratio than 1:5, the extraction yield cannot achieve as higher as 1:5 cocoa-solvent ratio. As a conclusion, caffeine can be extracted from cocoa MCBC 1 seeds by using batch system. 60 minutes of extraction time, 400 of the particle size of cocoa seeds powder and 1:5 ratio of cocoa seed-solvent gives highest extraction yield of caffeine.